2016
DOI: 10.1097/igc.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Is Ovarian Cancer Being Managed According to Clinical Guidelines? Evidence From a Population-Based Clinical Audit

Abstract: Results support the need to reorganize the clinical pathway of patients with OC in the Piedmont Region and the need for better adherence to current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Knowing the real world is essential to start promoting changes in the treatment of EOC patients. Despite the fact that since 2004 the Italian national guidelines program has supported centralization for EOC patients 55 , several authors over time have highlighted a lack of centralization 56 which still seems to persist (Table 1 ) and that likely reflects into a suboptimal treatment of affected patients. The national health system, the scientific societies and first of all the individual specialists (gynecologists, oncologists, general surgeons, general practitioners) should guarantee all patients the most appropriate treatments by directing them to the centers with greater competence.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the real world is essential to start promoting changes in the treatment of EOC patients. Despite the fact that since 2004 the Italian national guidelines program has supported centralization for EOC patients 55 , several authors over time have highlighted a lack of centralization 56 which still seems to persist (Table 1 ) and that likely reflects into a suboptimal treatment of affected patients. The national health system, the scientific societies and first of all the individual specialists (gynecologists, oncologists, general surgeons, general practitioners) should guarantee all patients the most appropriate treatments by directing them to the centers with greater competence.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 studies grouped under guideline adherence and deviation, 8 utilised the NCCN ovarian cancer guidelines as the comparator guideline, with 3 using their own local or national guidelines [3,[17][18][19][20][21][22][23][24][25][26]. These studies collectively indicated variation in adherence to guidelines for both surgical staging and receipt of chemotherapy.…”
Section: Guideline Adherence and Deviationmentioning
confidence: 99%
“…They can highlight potential quality concerns, identify areas that need further study and investigation, track changes over time, and enable physicians to compare their practices with the guidelines and with each other, in order to strive for optimal health care [3,4]. Recent literature shows that less than 50% of patients suffering from ovarian cancer in Europe are treated according to the guidelines and that there is a correlation between treatment adherent to the guidelines and survival [5]. This is a striking example demonstrating that there is a high need for quality control and benchmarking in our health care systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although international organizations such as ESMO and ESGO have provided guidelines on the treatment of gynaecological cancers, up to now no agreement has been reached on the proper QI’s which could be used to measure and benchmark the quality of the provided care [ 7 , 13 15 ]. Therefore, we decided to perform an online survey for specialists involved in the treatment of patients with endometrial, cervical and ovarian cancer to question the acceptability and practicability in daily practice of the QI’s which were distilled out of our literature search [ 5 ].…”
Section: Introductionmentioning
confidence: 99%